Vietnam : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper seeks to assess how this transformation has affected its growth potential. Employing a range of methodologies, the analysis concludes that Vietnam's medium-term growth potential has increased from 6.2 percent estimated in 2014 to 6.5 percent. Acceleration of reforms that have generated productivity gains in the last decade, including the implementation of agreed free trade agreements, could further boost growth potential. The four methodologies provide a range of estimates for Vietnam's potential output. On balance, we assess the potential growth estimate in Vietnam to be at 6.5 percent in 2017, higher than previous staff estimates of 6.2. The output gap is estimated at 0.4 percent in 2017. This analysis will be extended further in a forthcoming paper. The production function estimates can be further improved by explicitly incorporating the effect of structural transformation due to labor reallocation into the model, and by better accounting for the impact of the quality of human capital accumulation by taking the quality of education into account. Improvements in data quality, for example, on real estate prices, quarterly gross domestic product, unemployment rate and labor force in the informal sector, and capacity utilization, could further enhance the analysis.